1995
DOI: 10.1136/gut.37.3.394
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous colitis in Orebro, Sweden, an epidemiological study 1984-1993.

Abstract: The incidence and prevalence of collagenous colitis are unknown. An epidemiological study was undertaken between 1984-93. All patients living in the immediate catchment area of Orebro Medical Center Hospital with the diagnosis collagenous colitis were identified. Biopsy specimens classified as unspecific intestinal fibrosis were re-examined to identify cases not correctly diagnosed at first. Medical records were scrutinised and colorectal biopsy specimens re-evaluated. Thirty patients with collagenous colitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
111
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 13 publications
(1 reference statement)
5
111
0
2
Order By: Relevance
“…Studies from different countries reported microscopic colitis rates between 4%-13% in the cohor t of population with non-bloody diarrhea of unknown origin [10][11][12][13][14][15] . In the current study, we found this rate to be 11.5% in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies from different countries reported microscopic colitis rates between 4%-13% in the cohor t of population with non-bloody diarrhea of unknown origin [10][11][12][13][14][15] . In the current study, we found this rate to be 11.5% in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reported prevalence seems to change within years. In Sweden, microscopic colitis was reported in 4% of patients with non-bloody chronic diarrhea in 1993, but this rate was reported as 10% in 1998 [9,10,13] . The prevalence of collagenous colitis in Sweden between 1984-1988 was 0.8/10 5 inhabitants, but increased to 6.1/10 5 inhabitants between 1996-1998 [9,10,13,15] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations